"Do you like my body?": an interpersonal approach to the growth of bikini competitors on YouTube - Beytin, Brooke, author; Williams, Elizabeth A., advisor; Marx, Nick, committee member; Ogle, Jennifer, committee member (Colorado State University. Libraries, 2017)
This study investigates the popularity growth of bikini competitors on the social media outlet of YouTube. This content falls into the category of "fitspiration" content, otherwise known as fitness social media content that advocates for health and well-being. While fitspiration content has been shown to be damaging to the consumer regarding body image and self-esteem, consumers are increasingly choosing to engage with it. Therefore, this project takes an audience approach, probing why this phenomenon is spreading rapidly regardless of its potentially harmful effects. Using a qualitative interview approach, I explore the appeal of this YouTube content by interviewing women who actively engage with the YouTube videos of bikini competitors. I utilize three communication theories—social identification theory, parasocial interaction theory, and narrative theory—to explore why the fitspiration YouTube content of bikini competitors is becoming more popular. The findings indicate that all three theories play a role in drawing women to fitspiration content, although identification seemed to be the most reported factor. The findings not only provide valuable insights about the appeal of fitspiration content, but also about the potentially damaging effects of fitness-related social media and bikini competitions regarding privilege, body image, and expectations of media consumers.
Do you like my body?: an interpersonal approach to the growth of bikini competitors on YouTube
Keywords: fitspiration; interpersonal; fitness; social media; health